ASSESSING SUPPLY CHAIN MANAGEMENT OF FREIGHT IN INTERMODAL TRANSPORT SYSTEM IN NIGERIA. - TEMITOPE, P. B.; OLUSEGUN, O. A.; OGOLA, D. B. (INTERNATIONAL JOURNAL OF: SOCIAL SCIENCE RESEARCH AND ANTHROPOLOGY, 2023)
The movement of goods is crucial to the economic survival of any nation. It is the means by which goods are distributed for consumption, disposition and production. The problem with Nigerian supply chain management of goods is characterized by delay in delivery, bad roads, missing or damages resulting to claims and defective packaging. This paper identified challenges confronting freight movement in supply chain management and determined the delay causative factors in logistics of the selected transportation companies. Lagos State was chosen as one of the States in Nigeria with the presence of all modes of transportation. Four transportation companies out of seven with Plc. status viz: MPZ Haulge, Muahlb Ltd, STL Logistics, and Ajahi Logistics were selected because they have depots at each geopolitical zone in Nigeria. The composition of supply chain managers and warehouse supervisors and logistics manager were the targeted respondents. Of the 307 respondents of this targeted population, 275 (89.6%) responses were retrieved from systematic random sampling technique of the selected companies. Research instrument was designed through Google forms and collected data was analyzed with One-sample T-test. Secondly, delay causative factors were analyzed with descriptive bar chart. Results revealed the challenges confronting freight logistics and causative delay factors in supply chain management ranging from taxes on the road, civil unrest, documentation, surge in demand and sourcing for trucks. The research concluded with some recommendations for government and companies.
The movement of goods is crucial to the economic survival of any nation. It is the means by which goods are distributed for consumption, disposition and production. The problem with Nigerian supply chain management of goods is characterized by delay in delivery, bad roads, missing or damages resulting to claims and defective packaging.
Keywords: Supply chain management; freight; transportation; mode; Nigeria